2005
DOI: 10.1093/toxsci/kfi285
|View full text |Cite
|
Sign up to set email alerts
|

Brief Postnatal PBDE Exposure Alters Learning and the Cholinergic Modulation of Attention in Rats

Abstract: Polybrominated diphenyl ethers (PBDEs), chemicals commonly used as flame retardants, are ubiquitous in the environment and bioaccumulate in humans and wildlife. However, little is known about their potential toxicological properties. In the present study, male Long-Evans rats orally administered the commercial PBDE mixture DE-71 or corn oil for 1 week, beginning at postnatal day (PND) 6, were tested on a visual discrimination task and two sustained attention tasks. After completion of these tasks, the rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 50 publications
3
74
0
Order By: Relevance
“…This result is in agreement with in vitro data obtained using cultured rat striatal synaptosomes exposed to PBDE, which found decreased DA in the synaptosomes [11], and an in vivo study in mice showing that DE-71 exposure caused a significant decrease in striatal DA and DOPAC [12]. It has also been shown that other environmental contaminants such as PCBs can affect dopaminergic signaling [29].…”
Section: Acc E P Ted P R E P R I Ntsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with in vitro data obtained using cultured rat striatal synaptosomes exposed to PBDE, which found decreased DA in the synaptosomes [11], and an in vivo study in mice showing that DE-71 exposure caused a significant decrease in striatal DA and DOPAC [12]. It has also been shown that other environmental contaminants such as PCBs can affect dopaminergic signaling [29].…”
Section: Acc E P Ted P R E P R I Ntsupporting
confidence: 92%
“…All rights reserved neurotransmitter system [10], and have neurotoxic effects on DA homeostasis, glutamatergic neurotransmission, and locomotor behavior [11,12]. In this regard, dopaminergic neurons are particularly interesting because they are known to play a critical role in motor control, cognition, motivation, and reward associated behavior, as well as endocrine regulation [13,14].…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Starting on PND 30, animals were tested in a visual discrimination learning task, in which they performed significantly worse than controls. In contrast, DE-71 did not alter sustained attention or inhibitory control, though treated animals were sub-sensitive to the effect of the cholinergic muscarinic antagonist scopolamine on attention (Dufault et al 2005). Finally, in a study (presented, however, only in abstract form) in which DE-71 was given to rats from GD 6 to PND 21 at the doses of 5, 30 and 100 mg/kg, tests of fear conditioning revealed a dose-dependent decrease in cue-but not context-based performance in male offspring tested as adults (Taylor et al 2003).…”
Section: Behavioral Studiesmentioning
confidence: 68%
“…In another postnatal exposure study, Long-Evans rats were given the pentaBDE mixture DE-71 by gavage from PND 6 to 12 (Dufault et al 2005). Starting on PND 30, animals were tested in a visual discrimination learning task, in which they performed significantly worse than controls.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…However, PBDE neurotoxicity has been observed absent impacts on TH regulation, suggesting other mechanistic pathways. Indeed, a growing body of evidence suggests that PBDE mechanisms of neurotoxicity may operate by several pathways that include disrupted TH signaling, altered cholinergic neurotransmissions 215,216 ; impaired neuronal proliferation and plasticity, 191,214,217 and oxidative stress. 218,219 While the underlying mechanisms of PBDE neurotoxicity are unclear, continued testing in fish would be informative to better understand these underlying mechanisms of PBDEs effects on the development and functioning of the central and peripheral nervous systems of vertebrates.…”
Section: Toxicity Mechanisms and Thyroid Interactionsmentioning
confidence: 99%